Figures Of Speech In The Uzbek And English Languages And Their Communicative Functions (Open Academia: Journal of Scholarly Research, 2025)
This article investigates how figures of speech are used in both the Uzbek and English languages, focusing on their roles in communication. The author compares rhetorical devices like metaphor, irony, and hyperbole, examining their functions in conveying meaning in each language. Through a comparative analysis of linguistic data, the article highlights how cultural contexts influence the interpretation and impact of these figures of speech. While similarities exist between the two languages, the study reveals that cultural differences affect the way these devices are applied. The research offers valuable insights into cross-cultural communication and the importance of rhetorical devices in both Uzbek and English-speaking communities